Heaven below : early pentecostals and American culture - Wacker, Grant, 1945- (Harvard University Press, 2003)
In this history of the rise of pentecostalism in the United States, Grant Wacker gives an in-depth account of the religious practices of pentecostal churches as well as an engaging picture of the way these beliefs played out in daily life.